L‐arginine or tempol supplementation improves renal and cardiovascular function in rats with reduced renal mass and chronic high salt intake. (25th February 2013) - Carlström, M.; Brown, R. D.; Yang, T.; Hezel, M.; Larsson, E.; Scheffer, P. G.; Teerlink, T.; Lundberg, J. O.; Persson, A. E. G.
Abstract Aim Early life reduction in nephron number and chronic high salt intake cause development of renal and cardiovascular disease, which has been associated with oxidative stress and nitric oxide (NO) deficiency. We investigated the hypothesis that interventions stimulating NO signalling or reducing oxidative stress may restore renal autoregulation, attenuate hypertension and reduce renal and cardiovascular injuries following reduction in renal mass and chronic high salt intake. Methods Male Sprague–Dawley rats were uninephrectomized (UNX) or sham‐operated at 3 weeks of age and given either a normal‐salt (NS) or high‐salt (HS) diet. Effects on renal and cardiovascular functions were assessed in rats supplemented with substrate for NO synthase (L‐Arg) or a superoxide dismutase mimetic (Tempol). Results Rats with UNX + HS developed hypertension and displayed increased renal NADPH oxidase activity, elevated levels of oxidative stress markers in plasma and urine, and reduced cGMP in plasma. Histological analysis showed signs of cardiac and renal inflammation and fibrosis. These changes were linked with abnormal renal autoregulation, measured as a stronger tubuloglomerular feedback (TGF) response. Simultaneous treatment with L‐Arg or Tempol restored cGMP levels in plasma and increased markers of NO signalling in the kidney. This was associated with normalized TGF responses, attenuated hypertension and reduced signs of histopathological changes in the kidney and in the heart. Conclusion Reduction in nephron number during early life followed by chronic HS intake is associated with oxidative stress, impaired renal autoregulation and development of hypertension. Treatment strategies that increase NO bioavailability, or reduce levels of reactive oxygen species, were proven beneficial in this model of renal and cardiovascular disease.